The Role of Reactive Oxygen Species in Antibiotic-Mediated Killing of Bacteria - Van Acker, Heleen; Coenye, Tom (Trends in microbiology (Regular ed.), 2017)
Recently, it was proposed that there is a common mechanism behind the activity of bactericidal antibiotics, involving the production of reactive oxygen species (ROS). However, the involvement of ROS in antibiotic-mediated killing has become the subject of much debate. In the present review, we provide an overview of the data supporting the ROS hypothesis; we also present data that explain the contradictory results often obtained when studying antibiotic-induced ROS production. For this latter aspect we will focus on the importance of taking the experimental setup into consideration and on the importance of some technical aspects of the assays typically used. Finally, we discuss the link between ROS production and toxin–antitoxin modules, and present an overview of implications for treatment. Bactericidal antibiotics induce cell death by a common mechanism involving the production of hydroxyl radicals. The contribution of ROS to antibiotic-mediated killing depends on the experimental conditions, and accurately quantifying ROS is not straightforward. Low ROS concentrations induce protective responses and resistance. The dual role of ROS is probably linked to the involvement of toxin–antitoxin modules in the regulation of ROS production. The induction of ROS upon antimicrobial treatment is not limited to antibiotics and prokaryotic cells.